AFTER ACTION REVIEW AS A PART OF THE EDUCATIONAL PROCESS IN MILITARY EDUCATIONAL INSTITUTIONS - Mynko, Oleksandr; Morozov, Ihor (Honor and Law, 2023)
The requirements of the governing documents regarding the organization of the analysis of the conducted actions ‒ After action Review, as a part of the internal communication work in the educational process and during the preparation and conduct of combat operations (conducting special operations) were analyzed. The experience of NATO member countries in implementing of the After Action Review conducted in the process of training and training of troops is considered. The relevance of the After Action Review and its role and place in the Lessons Learned System at the current stage of development of the security and defense forces of Ukraine are emphasized. The existing methodology for the implementation of the After Action Review in the training process and during the preparation and conduct of combat operations (conducting special operations) was analyzed. Prospects for the mandatory implementation of the process of studying the After Action Review methodology in military educational institutions and the expected effect were considered. It is expected that this will significantly contribute to the formation of commanders' growth mindset, which will transform consciousness and significantly improve the understanding of conclusions from the acquired training and combat experience. It will also allow to finally get rid of the fixed mindset that blocks any positive changes. In view of the ongoing Russian-Ukrainian war, the need for accelerated implementation of NATO standards ‒ the security and defense forces of Ukraine must undergo a process of important changes in the field of After Action Review process, Lessons Learned and exchange of combat experience as soon as possible.